2016
DOI: 10.3892/or.2016.4931
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptor β1 suppresses proliferation and migration by inhibiting PI3K/Akt signaling in human colorectal cancer cells

Abstract: Thyroid hormone receptor β1 (TRβ1) is a ligand‑dependent transcription factor that belongs to the superfamily of nuclear receptors. TRβ1 has been found to act as a tumor suppressor in many solid tumors including breast cancer and hepatocellular carcinoma, but its role in the progression of human colorectal cancer (CRC) remains unclear. In this study, microarray data analysis revealed that TRβ1 mRNA was downregulated in CRC tumors compared with that in the normal counterparts in both The Cancer Genome Atlas (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The Akt signaling pathway principally regulates the activity of cancer cells (30,31). Previous studies have indicated that the Akt signaling pathway is a key factor in the viability and migration of a number of types of tumor including colorectal (32), and prostate cancer (33), and glioblastoma (34) and osteosarcoma (35). Additionally, the Akt signaling pathway is an important regulator of breast cancer (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The Akt signaling pathway principally regulates the activity of cancer cells (30,31). Previous studies have indicated that the Akt signaling pathway is a key factor in the viability and migration of a number of types of tumor including colorectal (32), and prostate cancer (33), and glioblastoma (34) and osteosarcoma (35). Additionally, the Akt signaling pathway is an important regulator of breast cancer (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Because thyroxin affects important metabolic pathways such as AMPK (Adenosine 5’-monophosphate (AMP)-activated protein kinase) pathway and PI3K/Akt pathway, altered levels of metabolites in patients with hypothyroxemia have been the focus of many thyroid disease studies [1416]. In recent years, metabolomic studies have provided the advanced methods necessary to identify changing metabolite levels, resulting in rapid progress in disease biomarker discovery [1719].…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned effects of m-TRβ1 were significantly stronger than those of TRβ1. Studies have shown that TRβ1 can inhibit the proliferation and migration of hepatocarcinoma cells and other cancer cells [ 2 , 4 , 6 , 15 , 23 25 ]. Cell apoptosis is a complicated biological process that is associated with complex signaling pathway responses.…”
Section: Discussionmentioning
confidence: 99%
“…TRs regulate target gene transcription by interacting with specific DNA sequences, known as thyroid hormone response elements (TREs) [ 3 ]. Several recent studies have strongly suggested that TRβ plays an important role in cell proliferation and malignant transformation [ 4 7 ]. Low or even no expression of TRs and alterations in TR genes, especially TRβ1, have been identified in many types of cancer [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%